Maternal Folic Acid Supplementation, Dietary Folate Intake, and Low Birth Weight: A Birth Cohort Study - Yang, Liping; Wang, Wenjuan; Mao, Baohong; Qiu, Jie; Guo, Huaqi; Yi, Bin; He, Xiaochun; Lin, Xiaojuan; Lv, Ling; Xu, Xiaoying; Liu, Qing; Cao, Yongchun; et al. (Frontiers in Public Health, 2022)
Objectives To investigate the independent and collective effects of maternal folic acid supplementation or dietary folate intake on the risk of low birth weight (LBW), and to further comprehensively examine the joint associations of folic acid supplementation and dietary folate intake with LBW by various clinical subtypes. Design Participants were recruited from Gansu Provincial Maternity and Child Care Hospital. A standardized and structured questionnaire was distributed to collect demographic factors, reproductive and medical history, occupational and residential history, physical activity, and diet. Data on pregnancy-related complications and birth outcomes were extracted from medical records. Unconditional logistic regression models were used to estimate the odds ratio (OR) and 95% confidence interval (95% CI) for single and joint associations of folic acid supplementation and dietary folate intake with LBW. Setting A birth cohort data analysis using the 2010–2012 Gansu Provincial Maternity and Child Care Hospital in Lanzhou, China. Participants In total, 9,231 pregnant women and their children were enrolled in the study. Results Compared with non-users, folic acid supplementation was associated with a reduced risk of LBW (OR: 0.80, 95% CI: 0.66–0.97), and the reduced risk was mainly seen for term-LBW (OR: 0.59, 95% CI: 0.41–0.85), and multiparous-LBW (OR: 0.72, 95% CI: 0.54–0.94). There were no significant associations between dietary folate intake and LBW, and there was no interaction between folic acid supplement and dietary folate intake on LBW. Conclusions Our study results indicated that folic acid supplementation was associated with a reduced risk of LBW, and there was no interaction between folic acid supplements and dietary folate intake on LBW.